Effective location of thyristor controlled series capacitor by sensitivity based method for congestion management - Noorsakinah Abu Bakar, 1986-, author 639133; Mohd. Wazir Mustafa, supervisor 635914; Fakulti Kejuruteraan Elektrik 540663 (2015)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2015